Analysis of the indicators of athletes at leading sports schools in swimming - Ivanenko, S.; Tyshchenko, V.; Pityn, M.; Hlukhov, I.; Drobot, K.; Dyadechko, I.; Zhuravlov, I.; Omelianenko, H.; Sokolova, O. (Journal of Physical Education and Sport, 2020)
The purpose of the research - to evaluate the level of theoretical knowledge and practical skills of young athletes of Zaporizhzhia and Kherson sport schools in swimming. Material and Methods.The study involved beginner athletes, students of the Zaporizhzhia swimming School (ZapSwS) (59 people) and Kherson swimming school (KherSwS) (55 people), the total number - 114 persons, 25 honored trainers of Ukraine. The following research methods were used to solve the tasks in the work:analysis and synthesis of literature of the research topic; pedagogical observations; questionnaire of the sportsmen of Zaporizhzhia and Kherson swimming schools; analysis of the swimming curriculum; expert evaluation of coaches to determine the level of theoretical knowledge of sportsmen of the Zaporizhzhia and Kherson swimming schools; testing the level of theoretical knowledge of swimmers on the basis of questioning; standard methods of mathematical statistics. The object of study is the indicators of the theoretical knowledge and practical skills of young athletes Zaporizhzhia and Kherson sport schools in swimming. Results. The expert evaluation of the trainers shows a rather low level of theoretical knowledge among the students of the Zaporizhzhia schools of swimming "ZapSwS" and "KherSwS" on the following issues: selection of exercises to improve the movements of the legs and body in butterfly, methodology of training athletes in training backstroke. The average grade of theoretical knowledge did not exceed 4.6 points. The conducted pedagogical researches make it possible to state the fact that the existing number of training hours, which are allocated for the acquisition of knowledge and skills in swimming, does not allow almost 90% of athletes to learn even the main sports ways of swimming. Conclusions. The level of theoretical knowledge and practical skills of swimmers are satisfactory.